Residuos de bromopropilato en citrus limon, variedad Verna - Camara, M.A.=700 1 Barba, A.; Navarro Garcia, S.; Callizo, F.J.; Escribano, J.A.; Lopez de Hierro, N.
(Es, En)
ilus., 7 ref.
Keywords: ACARICIDAS; RESIDUOS; CITRUS LIMON; ESPAÑA; BROMOPROPILATO